Harnessing social innovation for energy justice: A business model perspective. (August 2017) - Hiteva, Ralitsa; Sovacool, Benjamin
Abstract: This paper uses a business model framework to discuss how principles of energy justice - in particular, equitable distribution of costs and benefits, affordability, due process and greater participation in decision-making - can be embedded in business model innovations for energy, through social innovation. The paper discusses four cases at different scales (local, subnational, regional and global) to highlight opportunities for introducing principles of energy justice into the core of business models of companies. By doing so, the paper offers a critical perspective on the potential of business model innovation to be guided through a more broadly defined understanding of value enhanced by concepts of energy justice. The discussion of the four case studies—the Carbon Cooperative, Robin Hood Energy, RenEsco, and the Yansa Community Interest Company—highlights the importance of creating supportive wider environments for social and business model innovations, such as the development of skills, knowledge and social capital, through interventions coming from multiple levels and focused on different aspects of energy generation, supply and use (i.e. finance and technical implementation). Going against the grain of current policy, the study implies a shift away from upscaling innovations by taking them to the national scale, and towards creating supportive conditions for more local deals in different geographic locations. Highlights: Energy justice lacks engagement with business literature and innovation. Social innovations can act as a bridge between business interests and energy justice. Policy should focus on creating supportive conditions for local pro-justice energy companies. Supportive environments should focus on all aspects of energy at all scales. Energy justice may be operationalised through market principles but not through the market alone.